Geographical variation in preventable hospital admissions for dental conditions: An Australia‐wide analysis. (24th October 2019) - Crocombe, Leonard A.; Allen, Penny; Bettiol, Silvana; Khan, Shahrukh; Godwin, Diana; Barnett, Tony; Hoang, Ha; Goldberg, Lynette R.
Abstract: Objective: To describe the characteristics of hospital admissions for dental conditions, by Australian Statistical Geography Standard remoteness area for the 5 years 2010/2011 to 2014/2015. Design: Retrospective analysis of preventable hospital admissions due to dental conditions. Setting: National data set provided by the Australian Institute of Health and Welfare. Participants: Every hospital admission for patients who were admitted for dental conditions over five financial years, from 2010/2011 to 2014/2015. Main outcome measures: The number (and rate per 1000 population) of hospital admissions due to dental conditions in each Australian Statistical Geography Standard remoteness area (major city, inner regional, outer regional, remote and very remote). Results: There were 316 937 hospital admissions for dental conditions over the 5‐year period. The rate of potentially preventable dental hospital admissions ranged from an average of 2.5 per 1000 population in major cities to 3.2 in inner regional areas, 3.1 in outer regional areas, and 4.1 per 1000 in remote and very remote areas. The rate of admissions was highest among those aged 0‐14 years living in remote (9.0‐10.0 per 1000) and very remote (9.8‐12.5 per 1000) areas. Dental caries was the most common reason for admissions. Conclusions: There is an urgent need to address the social determinants of oral health in children aged 0‐14 years living in remote and very remote Australia. The delivery of mobile primary dental care services needs to be expanded in remote and very remote areas to prevent and treat dental caries.